Transcriptome Variations in Verticillium dahliae in Response to Two Different Inorganic Nitrogen Sources - Tang, Chen; Li, Wenwen; Klosterman, Steven J.; Wang, Yonglin (Frontiers in Microbiology, 2021)
The fungus Verticillium dahliae causes vascular wilt disease on hundreds of plant species. The main focus of the research to control this fungus has been aimed at infection processes such as penetration peg formation and effector secretion, but the ability of the fungus to acquire and utilize nutrients are often overlooked and may hold additional potential to formulate new disease control approaches. Little is known about the molecular mechanisms of nitrogen acquisition and assimilation processes in V. dahliae. In this present study, RNA sequencing and gene expression analysis were used to examine differentially expressed genes in response to the different nitrogen sources, nitrate and ammonium, in V. dahliae. A total of 3244 and 2528 differentially expressed genes were identified in response to nitrate and ammonium treatments, respectively. The data indicated nitrate metabolism requires additional energy input while ammonium metabolism is accompanied by reductions in particular cellular processes. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses of DEGs during nitrate metabolism revealed that many of the genes encoded those involved in protein biosynthetic and metabolic processes, especially ribosome and RNA polymerase biosynthesis, but also other processes including transport and organonitrogen compound metabolism. Analysis of DEGs in the ammonium treatment indicated that cell cycle, oxidoreductase, and certain metabolic activities were reduced. In addition, DEGs participating in the utilization of both nitrate and ammonium were related to L-serine biosynthesis, energy-dependent multidrug efflux pump activity, and glycerol transport. We further showed that the mutants of three differentially expressed transcription factors (VdMcm1, VdHapX, and VDAG_08640) exhibited abnormal phenotypes under nitrate and ammonium treatment compared with the wild type strain. Deletion of VdMcm1 displayed slower growth when utilizing both nitrogen sources, while deletion of VdHapX and VDAG_08640 only affected nitrate metabolism, inferring that nitrogen assimilation required regulation of bZIP transcription factor family and participation of cell cycle. Taken together, our findings illustrate the convergent and distinctive regulatory mechanisms between preferred (ammonium) and alternative nitrogen (nitrate) metabolism at the transcriptome level, leading to better understanding of inorganic nitrogen metabolism in V. dahliae.